Fuzzy based implicit sentiment analysis on quantitative sentences [electronic resource] - Yazdavar, Amir Hossein, 1988- (2013)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2013